1999
DOI: 10.3168/jds.s0022-0302(99)75509-8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Whey Phospholipids

Abstract: A freeze-dried whey powder was produced by microfiltration of Cheddar cheese whey. A 0.2-micron ceramic membrane in a stainless steel housing unit was used to concentrate components > 400 kDa present in the whey. The experimental whey powder, derived from Cheddar cheese whey, and a commercial whey powder were subjected to proximate analysis, lipid classes, phospholipid classes, and fatty acid compositional analyses. Commercial whey powder and commercial soybean lecithin were subjected to an alcohol fractionati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 9 publications
4
20
1
Order By: Relevance
“…Although differences being smaller, they remained highly significant (p < 0.01) and the main reason for this could be a different type of aggregation of lipids in the case whey buttermilk but also the presence of casein micelles in the CP layer in the case of regular buttermilk. Also it is known that the fat recovered in the whey cream is partly composed of free lipids (Fox et aI., 2000) (Scott, Duncan, Sumner, Waterman, & Kaylegian, 2003) whereas this number was close to 90% for commercial whey (Boyd, Drye, & Hansen, 1999). Surel (1993) has shown that long chain fatty are better retained by MF (0.2 J.lm) as compared to short chain fatty acids.…”
Section: Microfiltration Permeation Flux Datamentioning
confidence: 96%
“…Although differences being smaller, they remained highly significant (p < 0.01) and the main reason for this could be a different type of aggregation of lipids in the case whey buttermilk but also the presence of casein micelles in the CP layer in the case of regular buttermilk. Also it is known that the fat recovered in the whey cream is partly composed of free lipids (Fox et aI., 2000) (Scott, Duncan, Sumner, Waterman, & Kaylegian, 2003) whereas this number was close to 90% for commercial whey (Boyd, Drye, & Hansen, 1999). Surel (1993) has shown that long chain fatty are better retained by MF (0.2 J.lm) as compared to short chain fatty acids.…”
Section: Microfiltration Permeation Flux Datamentioning
confidence: 96%
“…Bovine milk has usually been used as a source of PL for many industrial and nutritional applications, with egg and soybean lecithin as alternatives. Egg lecithin is mainly composed of PC (70%), PE (24%), SM (4%) and trace amounts of lyso-PC (LPC), lyso-PE, phosphatidylserine (PS) and phosphatidylinositol (PI) (Kuksis, 1992), while soybean lecithin contains PC (28%), PE (26%), PS/PI (30%), and LPC (16%), with no SM (Boyd et al, 1999). In both lecithins, the absence or the very low content of SM is remarkable.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…In both lecithins, the absence or the very low content of SM is remarkable. Regarding the fatty acid content of these lecithin products, soybean contains a very high proportion of unsaturated fatty acids (77%, with 66% of polyunsaturated) (Boyd et al, 1999), while egg lecithin has 54% of unsaturated fatty acids (21% polyunsaturated) (Kuksis, 1992). The high unsaturated fatty acid content of these products contrasts with the low content of bovine milk PL (31%) (Sánchez-Juanes et al, 2009a).…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…More purified phospholipids can be separated into two application categories, namely for oil-in-water or water-in-oil emulsions based on their hydrophilic-lipophilic balance (HLB) [Boyd et al, 1999].…”
Section: Isolation Of Mfgm From Industrial Sourcesmentioning
confidence: 99%